Teaching about Technology - de Vries, Marc J. author. aut Link
IX, 172 p.
Keywords: Teaching about technology, at all levels of education, can only be done properly when those who teach have a clear idea about what it is that they teach. In other words: they should be able to give a decent answer to the question: what is technology? In the philosophy of technology that question is explored. Therefore the philosophy of technology is a discipline with a high relevance for those who teach about technology. Literature in this field, though, is not always easy to access for non-philosophers. This book provides an introduction to the philosophy of technology for such people. It offers a survey of the current state-of-affairs in the philosophy of technology, and also discusses the relevance of that for teaching about technology. The book can be used in introductory courses on the philosophy of technology in teacher education programs, engineering education programs, and by individual educators that are interested in the intriguing phenomenon of technology that is so important in our contemporary society.